2018
DOI: 10.1111/srt.12645
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical properties of striae rubra and striae alba in human skin: Comparison with normal skin

Abstract: Background Striae distensae are common dermal lesions that progress through two different stages: the striae rubra, which appears to be erythematous, and striae alba, which is characterized by a hypopigmented feature. The clinical characteristics between striae distensae stages and normal skin remain unknown. Objectives We aimed to investigate the clinical characteristics according to stages of striae distensae in terms of their biophysical properties, using objective noninvasive measurements in comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…Stretch marks (“striae distensae”, SD) are benign dermal lesions that histologically resemble dermal scars 1 . Clinically and histopathologically two types of striae, distinct by their stage of maturation, exist: “striae rubrae” (SR), appearing initially as immature, tense, erythematous lesions, and later on “striae albae” (SA) with an appearance similar to dermal scars with atrophic, hypopigmented characteristics 2,3 . Histopathologically, SR show reorganisation and reduction of elastin and fibrillin fibres and structural changes of collagen.…”
Section: Introductionmentioning
confidence: 99%
“…Stretch marks (“striae distensae”, SD) are benign dermal lesions that histologically resemble dermal scars 1 . Clinically and histopathologically two types of striae, distinct by their stage of maturation, exist: “striae rubrae” (SR), appearing initially as immature, tense, erythematous lesions, and later on “striae albae” (SA) with an appearance similar to dermal scars with atrophic, hypopigmented characteristics 2,3 . Histopathologically, SR show reorganisation and reduction of elastin and fibrillin fibres and structural changes of collagen.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that SD are less viscoelastic than the normal skin area, being less elongated by negative pressure and less retracted when relaxed. Several previous studies investigated the biomechanical properties of SD using non‐invasive equipment such as Cutometer ® , Reviscometer ® , and Ballistometer ® . It has been shown that SD lesions are less elastic and less deformable than normal skin through a lower Coefficient of restitution (CoR) and Area parameters in Ballistometer ® and lower Ur/Ue, Ur/Uf, and Uf parameters in Cutometer ® Previous studies have stated that elastin degradation is one of the initial morphological changes of SD, and dermal elastin is fragmented and markedly decreased in SD .…”
Section: Discussionmentioning
confidence: 99%
“…These findings could support the instrumental assessment results of a lower elasticity of SD in our study. In addition, the changes in the dermis structure of SD were visualized using ultrasound scanning, represented as the echo‐low zone inside the dermis . The lower dermal density could also explain the reduced viscoelasticity of SD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations